Chinese expert consensus on the management of hydraulic-coupled intracranial pressure monitoring via external ventricular drainage. - FENG, Guang; SHI, Guang-zhi; WANG, Mei-yun; WANG, Xin-jun (Chinese Journal of Contemporary Neurology & Neurosurgery, 2025)
Intracranial pressure (ICP) monitoring serves as a critical component in the management of neurocritical care patients. Hydraulic-coupled intracranial pressure monitoring via external ventricular drainage (EVD-ICP) monitoring offers a clinically practical approach that enables both dynamic physiological assessment and therapeutic intervention, and has gained widespread adoption. However, the significant variability persists across healthcare institutions regarding the procedural standardization and the implementation of systematic management protocols. Building upon evidence-based medical principles and multidisciplinary expert consensus, this "Chinese expert consensus on the management of hydraulic-coupled intracranial pressure monitoring via external ventricular drainage" synthesizes key aspects of EVD-ICP monitoring, including clinical indications, procedural workflows, trouble shooting strategies, monitoring duration, complication prevention and management. The expert consensus aims to standard the technique and management of EVD-ICP monitoring, enhance diagnostic and therapeutic outcomes in the neurocritical care patients, and promote the standardized, precise and efficient application of this technology across clinical settings.